ANALYSIS OF COOKING STAFF NEEDS USING THE INDEX STAFFING NEEDS (ISN) AND WORKLOAD INDICATORS OF STAFFING NEEDS (WISN) METHOD IN THE NUTRITION INSTALLATION AT Dr. H ABDUL MOELOEK REGIONAL HOSPITAL OF BANDAR LAMPUNG: ANALYSIS OF COOKING STAFF NEEDS USING THE INDEX STAFFING NEEDS (ISN) AND WORKLOAD INDICATORS OF STAFFING NEEDS (WISN) METHOD IN THE NUTRITION INSTALLATION AT Dr. H ABDUL MOELOEK REGIONAL HOSPITAL OF BANDAR LAMPUNG - Nurhikmah, Nurhikmah; Junita, Dera Elva; Wati, Desti Ambar; Abdullah, Abdullah (STIKes Mitra Keluarga, 2024)
Introduction: An examination of energy requirements is necessary because an imbalance between working hours and workload andthe amount of energy available could lead to a significant risk of workplace mishaps. The research objective was to analyze the needfor cooking staff in the nutrition installation at the Dr.H Abdul Moeloek Regional Hospital of Bandar Lampung using the ISN and WISN methods, this is because from the 2023 report data, in one day the cooking staff serving meals to an average of 339 patients,whereas currently there are 29 cooking staff. Method: This research type is a qualitative analytical method using a cross-sectional design with an observation and interviewapproach. The research period is December 2023 to January 2024. The HR unit studied in this research is 29 cooking staff at theNutrition Installation at Dr. RSUD. H Abdul Moeloek Regional Hospital of Bandar Lampung. Result: The WISN approach yields 1.731,25 hours of total working time available, but the ISN method yields 1.737,50 hours/year.When the number of employees needed is taken into account, HR finds that the sub-units cooking staff has the greatest annual mainactivity of 784 minutes/year and the lowest annual main activity of 6076 minutes/year. The total result of all annual main activities forthe typical workload is 25090 minutes/year. The normal limit covers meeting activities, conversing, making personal phone calls,using the restroom, eating, and drinking. The criterion for the total allowance is 0.85. Conclusion: In the case of the ISN technique, where 38 people are needed for cooking staff, the shortage is 9 individuals; in the case of the WISN method, where 43 people are needed for cooking staff, the shortage is 14 people. Compared to ISN calculations, WISN calculations are more accurate and practical since they take into account the workload in the field.